Analisis Faktor-Faktor Penghambat Pengembangan Desa Digital Indonesia - Babys, Salomon Andreas; Prayitno, Edik; Benu, Eni (FISIP Universitas Bung Karno, 2024)
The national government has committed to turning 81,616 villages in Indonesia into digital villages, but this is still a discourse that has not been realized, there are many problems with efforts to create digital villages. This problem should not be a problem that is borne only by the government, but also by all elements of the nation, and therefore becomes a big homework for all elements of the nation, including the government and village communities. There are many obstacles and challenges that can influence the digital village development process in Indonesia. This research aims to explain the factors that influence the digital village program. This research uses an exploratory research method, which aims to obtain information and information as the initial data needed regarding digital villages. This research uses qualitative research with data collection methods using library research. The results of this research explain that the factors inhibiting the development of digital villages include the first factor: Human Resources, HR, the second factor is the facilities factor and the third factor is social support from all stakeholder elements. The solution to this problem is first; the need to build awareness for the entire community regarding the urgency and benefits of digital village development, secondly the importance of digital infrastructure development including solutions to the complexity of digital village building problems and thirdly, the need for collaborative support from all elements in digital village development both from educational institutions and the private sector. and the central government regarding policies that can encourage villages to develop digital villages.Keyword : Analysis, Barriers, Village, Digital, Indonesia